Odpowiedzi

Najlepsza Odpowiedź!
2009-11-19T23:46:10+01:00
2m³-m²=m²(2m-1)=(√3-1)²(2√3-2-1)=(3-2√3+1)(2√3-3)=(4-2√3)(2√3-3)=
8√3-12-12+6√3=14√3-24
dla m=√3-1
2009-11-19T23:46:52+01:00
2(√3 - 1)³ - (√3 - 1)² = 2(√3 - 1) * 2(√3 - 1)² - (√3 - 1)² // wyciągamy (√3 - 1)² przed nawias

(√3 - 1)² * ((2 * √3 - 2) - 1) = (√3 - 1)² * (2√3 - 3) =
= (3 - 2√3 + 1) * (2√3 - 3) = 6√3 - 9 - 12 - 6√3 +2√3 - 3 = 2√3

Pozdrawiam ;)
2009-11-19T23:50:30+01:00
M^3 = (sqrt(3)-1)^3 =
(√3)^3 - 3(√3)^2+3√3+1=
√3^3+3√3-9+1=
√3^3+3√3-8

m^2 = (sqrt(3)-1)^2 =
sqrt(3)^2 - 2sqrt(3)+1 = -2sqrt(3)+5

A równanie:
2(√3^3+3√3-8)-(-2sqrt(3)+5) = 2√3^3+6√3-16+2√3-5= 2√3^3+8√3-21



Albo w łatwiejszy spos:
wyciągamy przed nawias:

m^2(2m-1)
m^2 = -2√3+5
m = √3-1